2018
DOI: 10.3390/insects9020049
|View full text |Cite
|
Sign up to set email alerts
|

Spore Acquisition and Survival of Ambrosia Beetles Associated with the Laurel Wilt Pathogen in Avocados after Exposure to Entomopathogenic Fungi

Abstract: Laurel wilt is a disease threatening the avocado industry in Florida. The causative agent of the disease is a fungus vectored by ambrosia beetles that bore into the trees. Until recently, management strategies for the vectors of the laurel wilt fungus relied solely on chemical control and sanitation practices. Beneficial entomopathogenic fungi (EPF) are the most common and prevalent natural enemies of pathogen vectors. Laboratory experiments demonstrated that commercial strains of EPF can increase the mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Moreover, another entomopathogenic fungus, Isaria fumosorosea Wize (strain TR-78-3) (Ascomycota: Hypocreales), significantly reduced survival of X. compactus in laboratory trials both after direct application to the beetles and indirect treatment of hazelnut branches (Kushiyev et al 2018). Avery et al (2018) confirmed the susceptibility of X. crassiusculus to B. bassiana, I. fumosorosea and M. brunneum commercial strains, but spore acquisition by treated beetles was significantly higher after exposure to B. bassiana compared to the other two fungi. Mukasa et al (2019) observed more than 70% mortality of X. compactus in laboratory and field tests with an atoxigenic L-strain of Aspergillus flavus Link (Eurotiales: Trichocomaceae) isolated from Robusta coffee (Coffea canephora Pierre ex A. Froehner) farms in Uganda.…”
Section: Entomopathogenic Fungisupporting
confidence: 65%
“…Moreover, another entomopathogenic fungus, Isaria fumosorosea Wize (strain TR-78-3) (Ascomycota: Hypocreales), significantly reduced survival of X. compactus in laboratory trials both after direct application to the beetles and indirect treatment of hazelnut branches (Kushiyev et al 2018). Avery et al (2018) confirmed the susceptibility of X. crassiusculus to B. bassiana, I. fumosorosea and M. brunneum commercial strains, but spore acquisition by treated beetles was significantly higher after exposure to B. bassiana compared to the other two fungi. Mukasa et al (2019) observed more than 70% mortality of X. compactus in laboratory and field tests with an atoxigenic L-strain of Aspergillus flavus Link (Eurotiales: Trichocomaceae) isolated from Robusta coffee (Coffea canephora Pierre ex A. Froehner) farms in Uganda.…”
Section: Entomopathogenic Fungisupporting
confidence: 65%
“…The cryptic habit of the beetles warrants the repeated application of contact insecticides to avoid infestation and of systemic insecticides with long residual efficacy to kill those beetles already inside the trees (Paine et al, 2011;Castrillo et al, 2016;Eatough Jones and Paine, 2018). Early detection and sanitation measures are also implemented to dispose of infested wood and limit the spread of wood borers (Eatough Jones and Paine, 2015;Avery et al, 2018). A wide array of systemic fungicides has been tested to reduce the spread of ambrosia fungi, propiconazole being one of the most promising active ingredients so far (Mayfield et al, 2008;Freeman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, to achieve this, more information about the mechanisms of pathogenicity of this species is required. In this sense, it is assumed that the fungus is vectored by the insect, thus gaining free access to the host’s xylem [ 13 ], and FD is the consequence of fungal mass accumulation on stressed trees, among other possibilities [ 4 ]. Since Fusarium comprises many species that cause human and plant diseases worldwide [ 14 ], an important question would be to determine its contribution to pathogenesis.…”
Section: Introductionmentioning
confidence: 99%